2013
DOI: 10.1159/000354796
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chronic Obstructive Pulmonary Disease in Primary Care in Salzburg, Austria: Findings from the Real World

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a major public health burden and profoundly affects individuals suffering from the disease. However, the majority of subjects with COPD are still undiagnosed. Objectives: To evaluate COPD prevalence and detection strategies for COPD in the primary-care setting. Methods: The study was conducted in a random sample of general practitioner (GP) offices in Salzburg (Austria). A questionnaire and post-bronchodilator (PBD) spirometry was administered to pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 34 publications
0
35
0
3
Order By: Relevance
“…Furthermore, it is predicted to become the third leading cause of death worldwide by 2020 [3,4]. Recently, COPD has been recognized as a systemic disease; many patients with COPD have comorbidities that may have a significant impact on their quality of life and their prognosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is predicted to become the third leading cause of death worldwide by 2020 [3,4]. Recently, COPD has been recognized as a systemic disease; many patients with COPD have comorbidities that may have a significant impact on their quality of life and their prognosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information on characteristics of this study sample can be found elsewhere. 33 In the primary care validation sample, prevalence of PBD FEV 1 /FVC < LLN was 9.8%. Population characteristics (age, gender, smoking status and education) were not significantly different between the BOLD and the primary care based validation sample (data not shown).…”
Section: Resultsmentioning
confidence: 89%
“…33 Fifty percent of the invited primary care offices were willing to participate in this study. The patients’ mean participation rate in the offices was 12.5%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations